Smart Learning and Fourth Industrial Age Effects on Higher Education - Zitar, Raed (2021)
The shift toward e-learning is imminent. The world is heading to the fourth industrial age. What are the implications of the fourth industrial age on higher education? What can a trend such as artificial intelligence contribute to education? Can Blockchain technology play part in opening a new education model? Can credentials be awarded and granted online? Experts believe that market forces will push higher education institutes to expand online education. More hybrid learning spaces will be created and different degrees awarded, and curricula structures will be created in the few coming years. However, how will this affect the education, for the better or for the worse? We have investigated this major question through extensive research within available literature and through personal encounters with many stakeholders. What are the implications of the fourth industrial age on education? That would be a major question to answer.